Use of a continuous disinfection programme in commercial broiler production - D Beauzec; S McCarlie; RR Bragg (South African Journal of Animal Science, 2025)
The growing threat of antibiotic resistance necessitates the development of novel methods for addressing health management in animal production and reducing dependency on antibiotics. Biosecurity is a term that describes the various measures taken to reduce the introduction or proliferation of infectious material in the growth environment. Cleaning and disinfection are commonplace in broiler production; however, after chick placement, few further interventions are available to address possible negative health effects. In this study, a continuous disinfection programme using a modified quaternary ammonium compound-based disinfectant for drinking water application and direct spray was trialled at a commercial scale. The study evaluated two cleaning and disinfection protocols in four commercial poultry houses of 1800 m2 each in Stutterheim, in the Eastern Cape. Over two non-consecutive growth cycles, two houses underwent a standard cleaning and disinfection protocol (organic removal, pressure rinsing, surfactant foam, and aldehyde disinfectant), while two houses followed a continuous disinfection programme (Virukill®-based disinfection, followed by periodic mist spraying and waterline dosing). The test evaluated whether the compound could improve growth performance and mortality rates. The product may be a viable alternative to standard chemicals currently used in the industry for cleaning and disinfection, as the use of the continuous disinfection programme resulted in improved performance. The results further indicated that improved cleaning, as evaluated using viral methods, could serve as an indicator of performance.